2009
DOI: 10.1007/s10519-009-9324-6
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Conduct Problems and Maltreatment: Testing Genetic and Environmental Mediation

Abstract: It is often assumed that childhood maltreatment causes conduct problems via an environmentally mediated process. However, the association may be due alternatively to either a nonpassive gene-environment correlation, in which parents react to children’s genetically-influenced conduct problems by maltreating them, or a passive gene-environment correlation, in which parents’ tendency to engage in maltreatment and children’s conduct problems are both influenced by a hereditary vulnerability to antisocial behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…While such a prospective test will be valuable, it is also important to note that a meditational model in which parental PTSD leads to aggression, which leads to negative child outcomes, is likely overly simplistic. For instance, such a model does not account for "child-driven effects," which refer to offspring characteristics (e.g., temperament, behavior, gender) that evince particular parenting behaviors (e.g., Anderson, Lytton, & Romney, 1986;Ge et al, 1996) or the effects of shared genetic heritability on both parenting and child outcomes (e.g., Shulz-Heik et al, 2010). Further, these processes play out within a larger context comprised of myriad variables (e.g., poverty) that shape distinct developmental trajectories in terms of child outcomes (e.g., Bronfenbrenner, 1972Bronfenbrenner, , 1979O'Connor, 2002;Zielinski & Bradshaw, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…While such a prospective test will be valuable, it is also important to note that a meditational model in which parental PTSD leads to aggression, which leads to negative child outcomes, is likely overly simplistic. For instance, such a model does not account for "child-driven effects," which refer to offspring characteristics (e.g., temperament, behavior, gender) that evince particular parenting behaviors (e.g., Anderson, Lytton, & Romney, 1986;Ge et al, 1996) or the effects of shared genetic heritability on both parenting and child outcomes (e.g., Shulz-Heik et al, 2010). Further, these processes play out within a larger context comprised of myriad variables (e.g., poverty) that shape distinct developmental trajectories in terms of child outcomes (e.g., Bronfenbrenner, 1972Bronfenbrenner, , 1979O'Connor, 2002;Zielinski & Bradshaw, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…'), and serious neglect (`Were you ever seriously neglected as a child?'). This operationalization of childhood maltreatment (combining physical abuse, sexual abuse, and neglect) is frequently used in maltreatment research (Ireland & Widom, 1994; Schulz-Heik et al 2009; Topitzes et al 2009; Zielinski, 2009). Consistent with many prior studies of childhood maltreatment, we included childhood maltreatment if it occurred prior to age 15 years (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…If genetic mediation accounts for the CA-BPD association, then INT and EXT are heritable characteristics that might account for the CA-BPD association. Twin studies have shown that INT, EXT, and CA are each influenced by both genetic and shared environment factors (Bergen, Gardner, & Kendler, 2007; Bornovalova, Hicks, Iacono, & McGue, 2010; Burt, Krueger, McGue, & Iacono, 2001, 2003; Burt, McGue, Krueger, & Iacono, 2005a; Gjone, Stevenson, Sundet, & Eilertsen, 1996; Hicks, Krueger, Iacono, McGue, & Patrick, 2004; Kendler, Prescott, Myers, & Neale, 2003; Schulz-Heik et al, 2010) with heritability being moderate to high for INT and EXT and modest for CA (Jaffee, Caspi, Moffitt, & Taylor, 2004; Lyons et al, 1993; Schulz-Heik et al, 2010; Stein, Jang, Taylor, Vernon, & Livesley, 2002). Research has also demonstrated that genetic mediation can account for the association between childhood EXT and maladaptive parenting practices and abuse (Burt et al, 2003; Burt et al, 2005a; Schulz-Heik et al, 2010), and between adult violence and stress exposure with BPD (Distel et al, 2011).…”
mentioning
confidence: 99%